Exploring patient preferences for involvement in medication management in hospitals. (21st June 2019) - Bucknall, Tracey; Digby, Robin; Fossum, Mariann; Hutchinson, Alison M.; Considine, Julie; Dunning, Trisha; Hughes, Lee; Weir‐Phyland, Janet; Manias, Elizabeth
Abstract: Aim: The aim of this study was to identify patient preferences for involvement in medication management during hospitalization. Design: A qualitative descriptive study. Methods: This is a study of 20 inpatients in two medical and two surgical wards at an academic health science centre in Melbourne, Australia. Semi‐structured interviews were recorded and analysed using content analysis. Findings: Three themes were identified: (a) 'understanding the medication' established large variation in participants' understanding of their pre‐admission medication and current medication; (b) 'ownership of medication administration' showed that few patients had considered an alternative to their current regimen; only some were interested in taking more control; and (c) 'supporting discharge from hospital' showed that most patients desired written medication instructions to be explained by a health professional. Family involvement was important for many. Conclusion: There was significant diversity of opinion from participants about their involvement in medication management in hospital. Patient preferences for inclusion need to be identified on admission where appropriate. Education about roles and responsibilities of medication management is required for health professionals, patients and families to increase inclusion and engagement across the health continuum and support transition to discharge. Impact statement: Little is known about patient preferences for participation in medication administration and hospital discharge planning. Individual patient understanding of and interest in participation in medication administration varies. In accordance with individual patient preferences, patients need to be included more effectively and consistently in their own medication management when in hospital. Abstract : 目的: 本研究旨在确定患者在住院期间参与药物管理的偏好。 设计: 描述性定性研究。 方法: 对澳大利亚墨尔本一个学术健康研究中心的两个内科和两个外科病房的20名住院患者进行研究。使用内容分析记录和分析半结构化访谈。 研究结果: 确定了三大主题:(a)"了解药物"——参与者对其入院前用药和当前用药的了解有很大的差异;(b)"用药管理权"表明很少有患者考虑过对他们当前治疗方案的其他选择;只有一些人对对其采取更多的控制感兴趣, (c)"支持出院"表明, 大多数患者都希望得到由健康专家解释过的书面用药说明。家属涉入对许多人来说很重要。 结论: 参与者对其参与医院用药管理的看法存在显著差异。在适当的情况下, 入院时需要确定患者的参与偏好。卫生专业人员、患者及其家属需要接受有关用药管理的角色和责任的教育, 以增加整个治疗和支持过渡过程的范围和参与程度, 直至出院。 影响说明: 关于患者参与用药管理和出院计划的偏好知之甚少。患者对用药管理的了解和参与兴趣各不相同。根据患者的个人偏好, 患者在住院时需要更有效和一贯地纳入其用药管理事宜。